Inheritance and Contact in the Development of Lateral Obstruents in Nguni Languages (S40) - Nina van der Vlugt; Hilde Gunnink (Languages)
This study investigates the development of the lateral fricatives and affricates, to which we jointly refer as ‘lateral obstruents’, in Nguni (S40) languages of Southern Africa. These lateral obstruents, which include /ɬ, ⁿɬ, ɮ, ⁿɮ, k͡ʟ̝̊/, are rare in the Bantu language family, and are not reconstructed for Proto-Bantu. Lateral obstruents are also rare cross-linguistically. They do occur, however, in four sub-branches of Southern Bantu: Shona, Sotho-Tswana, Nguni, and Tsonga. In this paper, we study how Southern Bantu could have acquired such a large inventory of cross-linguistically rare phonemes by investigating their development in Nguni languages, a large but closely related cluster of languages in which lateral obstruents are very frequent. We analyze published data from nine Nguni languages, including languages for which the only available descriptions are dated or of limited scope, in which case we carefully assess the data and their analysis. On the basis of this large database, we show which lateral obstruents are used in Nguni, and the vocabulary in which they occur. Applying the Comparative Method, we show that alveolar lateral obstruents can be reconstructed to Proto-Nguni, where they are the regular reflex of Proto-Bantu palatals *c and *j. The velar lateral affricate, in contrast, cannot be reconstructed to Proto-Nguni, and finds its origin in loanwords, for example, from Khoe languages, where it is used as a click replacement strategy. As a result, we conclude that both inheritance and contact played a role in the development of lateral obstruents in Nguni, likely combined in the case of alveolar lateral obstruents. In order to better understand the contact history, we evaluate existing hypothesized contact scenarios to account for the presence of lateral obstruents in Southern Bantu or Nguni. Given that alveolar lateral obstruents result from a regular sound change, contact does not seem to be as prominent in the development of lateral obstruents as has been proposed before in the literature. This study lays the groundwork for future research into lateral obstruents in Southern Bantu.